Biorefining of Lignocellulosic Feedstock by a Modified Ammonia Fiber Expansion Pretreatment and Enzymatic Hydrolysis for Production of Fermentable Sugars. Issue 1 (2nd December 2016) - Kamm, Birgit; Leiß, Sebastian; Schönicke, Petra; Bierbaum, Matthias
Abstract: Wheat straw was pretreated and afterwards enzymatically hydrolyzed using a modified ammonia fiber expansion (AFEX) process under different reaction conditions to produce fermentable sugars. Instead of liquid ammonia, aqueous ammonia (25 % w / v ) was used to test its influence on the sugar concentration and yield of the sugars. It is shown that a protein extraction after the pretreatment can distinctly improve the result obtained for the enzymatic hydrolysis. This modified AFEX process using aqueous ammonia represents a simpler and less expensive variant of the AFEX process usually described in literature. Thus, the described process can be used for the primary refining of lignocellulosic feedstocks in the sense of a roadmap for biorefinery. Abstract : Dilute ammonia, get more sugars : Wheat straw is first pretreated using a modified ammonia fiber expansion (AFEX) process using a diluted aqueous ammonia solution. Extracting proteins from the reaction mixture has a distinct influence on the subsequent enzymatic hydrolysis, which produces fermentable sugars. This modified AFEX process using aqueous ammonia represents a simpler and less expensive variant of the AFEX process usually described in literature.